Cerebral Intricacies: Deciphering the Mystique of Primary Central Nervous System Angiosarcoma - Ahuja, Sana; Malik, Shaivy; Ahluwalia, Charanjeet (Asian Journal of Neurosurgery, 2025)
Angiosarcoma of the central nervous system (CNS) is an exceptionally rare and aggressive vascular malignancy presenting significant diagnostic and therapeutic challenges. We report the case of a 22-year-old female with CNS angiosarcoma, highlighting diagnostic intricacies, therapeutic approaches, and management outcomes. Initial symptoms included headache and dizziness, with magnetic resonance imaging revealing a space-occupying lesion in the right parietal lobe, initially misinterpreted as cavernoma. Subsequent surgical resection confirmed angiosarcoma histologically, supported by immunohistochemical analysis showing endothelial markers. Treatment comprised local irradiation postoperatively, resulting in no recurrence or metastasis. Histopathological examination revealed an infiltrative growth pattern with atypical endothelial cells forming irregular vascular spaces. Challenges in diagnosis arise due to overlapping features with other intracranial lesions. Multimodal treatment approaches involving surgery, radiation, and chemotherapy were employed, although their efficacy remains uncertain. Prognosis remains poor, underscoring the imperative for collaborative efforts to enhance understanding and management of this rare malignancy. Our case contributes valuable insights to the limited literature on CNS angiosarcoma, emphasizing the need for comprehensive case studies to refine diagnostic and therapeutic strategies.
Keywords: cerebral; angiosarcoma; central nervous system; cavernoma; epithelioid